Association of physical body-kinesthetic (Multiple Intelligences) mobility with learning results biology in SMA negeri 2 bandar lampung. (April 2020) - Pratama, Riandy; Handoko, Akbar; Anwar, Chairul
Abstract: Multiple Intelligences defines intelligence as the ability and skill of resolving problems, creating valuable products in one or more environments, cultures and communities. So that with multiple intelligences can affect the ability of students to learn specifically in learning Biology. This research aims (1) To know the relationship between students who have kinesthetic ability to learn Biology subjects (2) to know the difference in student grades based on kinesthetic indicators. The method used was the correlational method using 1 class as an experimental class as well using product moment formula. This research was held on May 29 until June 10, 2017 sample taken in class XI MIA I with purposive sampling technique. SMAN 2 Bandar Lampung mission is to develop the potential of learners Multiple Intelligences including intelligent motion. Refers to the bookSuharsimi Arikunto consists of 45 statements based on the indicator of kinesthetic ability, consisting of 5 indicators to look for differences in the value of each indicator using a one-way Anova Test. Collection of student value data on the pick up based on final exam results. The significant value between kinesthetic intelligence and the learning outcomes based on the analysis of the two interconnected interpretation is sufficient.